Fabled Territories : New Asian Photography in Britain. - City Art Gallery, Leeds; Viewpoint Gallery, Salford (Leeds : City Art Galleries, 1989)
Afza, Nudrat ; Bhimji, Zarina ; Biswas, Sutupa ; Burman, Chila Kumari ; C-Maan, Mujassam ; Das, Prodeepta ; Desai, Poulomi ; etc.
Fabled Territories : New Asian Photography in Britain, City Art Gallery, Leeds, 16 November - 7 January 1990 / Viewpoint Gallery, Salford, 3 March - 17 April 1990
boek